Completeness and coverage of open‐access freshwater fish distribution data in the United States. Issue 12 (13th September 2017) - Troia, Matthew J.; McManamay, Ryan A.
Abstract: Aim: Open‐access databases provide unprecedented access to records of species occurrence, but their utility depends on how complete species inventories are at given surveying resolutions and how uniformly distributed surveys are in space and time. Our aims were to assess (1) the completeness of freshwater fish surveys across spatial scales and among habitats and (2) survey coverage along spatial and temporal gradients. Location: Contiguous United States. Methods: We compiled occurrence records of freshwater fish species from the Global Biodiversity Information Facility, the Multi‐State Aquatic Resources Information Server and federally administered surveys. We evaluated survey completeness across seven spatial resolutions, and separately for lotic and lentic habitats using three thresholds of two survey completeness indices. We evaluated survey coverage from 1800 to 2016 and along climatic and local environmental gradients using histograms and Kolmogorov–Smirnov tests. Results: Over 21 million reliable abundance (>1.5 million incidence) records representing 892 species were available from 1800 to 2016. The proportion of catchments containing >1 record increased as spatial resolution coarsened, as did the proportion of surveyed catchments classified as well‐surveyed. Records were distributed among 37, 775 lotic reaches, but only 1, 626 lentic water bodies. Thirteen percentage of surveyed lotic reaches and 33% of surveyed lentic water bodies were well‐surveyed based on the most conservative completeness thresholds. Most well‐surveyed lotic reaches (94%) and lentic water bodies (96%) were surveyed since 1980. Climates representative of the west and gulf coasts as well as headwater streams and small ponds were under‐represented. Main conclusions: Contemporary surveys of freshwater fish communities are abundant and generally representative of environmental characteristics in the contiguous USA. Survey clustering within MARIS‐participating states highlights the value of state agency data for biodiversity science and should encourage participation in this—and similar—data compilation endeavours. Future work should focus on surveying more lakes and reservoirs, compiling historical data and filling environmental gaps.